2003
DOI: 10.1161/01.cir.0000078637.21322.d3
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Increased Atherosclerotic Wall Thickness Into High Shear Stress Regions Is Associated With Loss of Compensatory Remodeling

Abstract: Background-Atherosclerosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 28 publications
7
105
0
2
Order By: Relevance
“…Because flow velocity is associated with shear stress and artery diameters have been shown to remodel to keep wall shear stress constant (the Glagov phenomenon), 28,29 we performed secondary analyses in which we included baseline brachial artery diameter as a covariate for 2 measures of vascular function: baseline mean flow velocity and hyperemic mean flow velocity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Because flow velocity is associated with shear stress and artery diameters have been shown to remodel to keep wall shear stress constant (the Glagov phenomenon), 28,29 we performed secondary analyses in which we included baseline brachial artery diameter as a covariate for 2 measures of vascular function: baseline mean flow velocity and hyperemic mean flow velocity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In normal human coronary arteries, the time-averaged wall shear stress was previously determined to be ,16 dyn/cm 2 (Joshi et al, 2004;Stone et al, 2003;Wentzel et al, 2003). By contrast, the shear stress overlying plaques was .50 dyn/cm 2 (Gijsen et al, 2008;Stone et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Human and animal studies have shown that atherosclerotic regions with low ESS exhibit expansive remodeling. 1,4 -6,11,18 Wentzel et al 18 showed that as the atherosclerotic plaques grow and encroach into the lumen, the local ESS increases over the whole arterial cross section, including the nondiseased wall, which thereby promotes nitric oxidedependent compensatory expansive remodeling. However, the factors that determine whether the expansive remodeling response to atherosclerosis becomes either compensatory or excessive, with consequent implications fostering high-risk plaques, have not been studied previously.…”
Section: Interaction Of Low Ess With Excessive Expansive Remodeling Pmentioning
confidence: 99%